Poetry, Beauty, and Contemplation : The Complete Aesthetics of Jacques Maritain - Trapani, John G. (Book collections on Project MUSE., 2011)
"Poetry, Beauty, and Contemplation provides a basic introduction to, and an extensive examination of, Maritain's philosophy of art and beauty. The book begins with a brief biographical sketch of Maritain's early years, including the early influences on his philosophy (Henri Bergson and Thomas Aquinas among them). The author explores key terms and ideas central to Maritain's aesthetics -- intuition, connaturality, Poetry, and beauty -- and traces their historical development. The book integrates the inherent relationship between Maritain's unique understanding of "Poetry," his aesthetic and metaphysical ideas about beauty, and his explanation of the distinction between natural and supernatural contemplation, resulting in a complete exposition of Maritain's aesthetics."--Pub. website.